A comparative study of multimodality in English and Persian spam letters of advertising - Jalilifar, Alireza; Yazdani, Azam (Journal of Modern Languages, 2017)
The aim of this study is to identify patterns of multimodality and determine whether these patterns relate in any way to social and religious statuses of the Persian and English communities. To this end, by sending an announcement to an Iranian social network, network users were requested to forward their spam letters to one of the researchers’ emails. Then, 70 Persian and 70 English spam letters were randomly selected for the rhetorical analysis of the language mode and the image mode. The results of the study indicated that for the image mode, similar strategies were utilized in both Persian and English spam letters. However, some general distinctions were found in the images. For the language mode, clear differences were observed in the employment of rhetorical figures between the spams. Distinctions rooted in cultural and religious values account for the differences in applying the strategies for the image and language modes.